2018
DOI: 10.1186/s12905-018-0592-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weight loss intervention on body composition and blood pressure among overweight and obese women: findings from the MyBFF@home study

Abstract: BackgroundObesity is related to the increased incidence of hypertension and in healthy individuals, blood pressure changes with age and body mass. The aims of this paper were to evaluate the effectiveness of the weight loss intervention on body composition and blood pressure, and to evaluate the relationship between these factors among housewives in the MyBFF@home study.MethodsMyBFF@home intervention was a quasi-experimental study which involved 328 overweight and obese housewives aged 18–59 years old (Control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
1
18
0
1
Order By: Relevance
“…This nding is consistent with another study which showed that the mean diastolic blood pressure (DBP) and triglycerides decreased signi cantly in the intervention group in both sexes (36). A positive effect of life style modi cation on blood pressure has also been reported among Korean adults (37,38).…”
Section: Discussionsupporting
confidence: 90%
“…This nding is consistent with another study which showed that the mean diastolic blood pressure (DBP) and triglycerides decreased signi cantly in the intervention group in both sexes (36). A positive effect of life style modi cation on blood pressure has also been reported among Korean adults (37,38).…”
Section: Discussionsupporting
confidence: 90%
“…While individuals with higher body fat composition may be susceptible to metabolic disease, including hypertension [33], higher body fat in normal range of BMI was regarded to be a controversial risk factor for hypertension [34]. However, our study results showed that higher body fat was associated with increased odds of hypertension, suggesting that lowering body fat composition may increase the chance to control BP in normal-weight individuals [35]. Furthermore, the association between normal weight obesity and hypertension may differ by sex and age.…”
Section: Plos Onementioning
confidence: 51%
“…25,26 Also, The high percentage of body fat will cause stiffness in the endothelium and smooth muscle of blood vessels, inflammation in the perivascular area, and immune system dysfunction leading to an increase in blood pressure. 27 The results of this study also indicate that the percentage of body fat can be a good predictor for predicting the occurrence of cardiometabolic disease. 7 This is in line with research conducted by Phillips et al, which states that body fat percentage can be a better indicator for assessing obesity and the risk of other cardiometabolic diseases than body mass index (BMI).…”
Section: Discussionmentioning
confidence: 53%